2003
DOI: 10.1002/cne.10659
|View full text |Cite
|
Sign up to set email alerts
|

Localization of [3H]nicotine, [3H]cytisine, [3H]epibatidine, and [125I]α‐bungarotoxin binding sites in the brain of Macaca mulatta

Abstract: We determined the localization of [(3)H]nicotine, [(3)H]cytisine, [(3)H]epibatidine, and [(125)I]alpha-bungarotoxin binding sites in the brain of rhesus monkey by means of receptor autoradiography. The labelings by [(3)H]nicotine, [(3)H]cytisine, and [(3)H]epibatidine were highly concordant, except for epibatidine. Layer IV of some cortical areas, most thalamic nuclei, and presubiculum displayed high levels of labeling for the three ligands. Moderate levels of binding were detected in the subiculum, the septum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
45
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 65 publications
16
45
1
Order By: Relevance
“…The major nAChR receptor populations in cortex seem to contain ␣4␤2 subunits, in agreement with previous studies in rodents (Flores et al, 1992;Zoli et al, 2002;Champtiaux et al, 2003). In contrast, ␣2* nAChRs were also identified in monkey cortex, an observation consistent with the identification of ␣2 mRNA in monkey brain (Han et al, 2003). Both ␣4␤2 and ␣4␤2␣2 nAChRs seem to be present with this latter subtype representing ϳ16% of the ␣4␤2* cortical receptor population.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The major nAChR receptor populations in cortex seem to contain ␣4␤2 subunits, in agreement with previous studies in rodents (Flores et al, 1992;Zoli et al, 2002;Champtiaux et al, 2003). In contrast, ␣2* nAChRs were also identified in monkey cortex, an observation consistent with the identification of ␣2 mRNA in monkey brain (Han et al, 2003). Both ␣4␤2 and ␣4␤2␣2 nAChRs seem to be present with this latter subtype representing ϳ16% of the ␣4␤2* cortical receptor population.…”
supporting
confidence: 90%
“…In addition, monkeys with nigrostriatal damage exhibit symptoms that resemble those in Parkinson's disease, with the motor deficits reversed by the same drug used to treat this disorder. Studies have shown that the ␣2-␣7 and ␤2-␤4 nAChR transcripts are present in monkey substantia nigra (Han et al, 2000;Quik et al, 2000a,b) and that binding sites for 125 I-epibatidine, [ 3 H]cytisine, 125 I-A85380, 125 I-␣-conotoxin MII, and 125 I-␣-bungarotoxin are expressed in the striatum and substantia nigra (Quik et al, 2001;Kulak et al, 2002a,b;Han et al, 2003). Furthermore, there are differential changes in nAChRs after MPTP treatment, with a complete loss of 125 I-␣-conotoxin MII sites and also declines in ␣-conotoxin MII-resistant 125 Iepibatidine sites.…”
mentioning
confidence: 99%
“…nAChR subunit mRNAs in the primate nigrostriatal system include the α2, α4 through α7, and β2 through β4 transcripts [82,83]. Receptor binding studies with 125 I-epibatidine demonstrate that receptors are expressed in both the striatum and substantia nigra [84][85][86]. Subsequent studies with more selective ligands, such as 125 I-α-conotoxinMII indicated the presence of α6β2* nAChR subtypes, in the nigrostriatal system [84,87], while the use of 125 I-epibatidine in the presence of unlabelled α-conotoxinMII suggested the presence of α4β2* receptors.…”
Section: Monkeysmentioning
confidence: 99%
“…21) In rhesus monkeys, nAChRs a7 subtype distributes highest in the thalamus, moderate in the cortex and low in the cerebellum. [22][23][24][25] As shown in Fig. 4, successful images could be obtained.…”
Section: In Vivo Imaging Agents For Nachr A7 Sub-typementioning
confidence: 92%